Impacts of climate and land use changes on the hydrological and erosion processes of two contrasting Mediterranean catchments - Serpa, D. (2015)
The impacts of climate and land use changes on streamflow and sediment export were evaluated for a humid (São Lourenço) and a dry (Guadalupe) Mediterranean catchment, using the SWAT model. SWAT was able to produce viable streamflow and sediment export simulations for both catchments, which provided a baseline for investigating climate and land use changes under the A1B and B1 emission scenarios for 2071–2100. Compared to the baseline scenario (1971–2000), climate change scenarios showed a decrease in annual rainfall for both catchments (humid: − 12%; dry: − 8%), together with strong increases in rainfall during winter. Land use changes were derived from a socio-economic storyline in which traditional agriculture is replaced by more profitable land uses (i.e. corn and commercial forestry at the humid site; sunflower at the dry site). Climate change projections showed a decrease in streamflow for both catchments, whereas sediment export decreased only for the São Lourenço catchment. Land use changes resulted in an increase in streamflow, but the erosive response differed between catchments. The combination of climate and land use change scenarios led to a reduction in streamflow for both catchments, suggesting a domain of the climatic response. As for sediments, contrasting results were observed for the humid (A1B: − 29%; B1: − 22%) and dry catchment (A1B: + 222%; B1: + 5%), which is mainly due to differences in the present-day and forecasted vegetation types. The results highlight the importance of climate-induced land-use change impacts, which could be similar to or more severe than the direct impacts of climate change alone.